Diagnostic evaluation and cardiopulmonary exercise test findings in young athletes with persistent symptoms following COVID-19. Issue 16 (18th May 2022) - Moulson, Nathaniel; Gustus, Sarah K; Scirica, Christina; Petek, Bradley J; Vanatta, Caroyln; Churchill, Timothy W; Guseh, James Sawalla; Baggish, Aaron; Wasfy, Meagan M
Abstract : Objectives: Persistent or late-onset cardiopulmonary symptoms following COVID-19 may occur in athletes despite a benign initial course. We examined the yield of cardiac evaluation, including cardiopulmonary exercise testing (CPET), in athletes with cardiopulmonary symptoms after COVID-19, compared CPETs in these athletes and those without COVID-19 and evaluated longitudinal changes in CPET with improvement in symptoms. Methods: This prospective cohort study evaluated young (18–35 years old) athletes referred for cardiopulmonary symptoms that were present>28 days from COVID-19 diagnosis. CPET findings in post-COVID athletes were compared with a matched reference group of healthy athletes without COVID-19. Post-COVID athletes underwent repeat CPET between 3 and 6 months after initial evaluation. Results: Twenty-one consecutive post-COVID athletes with cardiopulmonary symptoms (21.9±3.9 years old, 43% female) were evaluated 3.0±2.1 months after diagnosis. No athlete had active inflammatory heart disease. CPET reproduced presenting symptoms in 86%. Compared with reference athletes (n=42), there was similar peak VO2 but a higher prevalence of abnormal spirometry (42%) and low breathing reserve (42%). Thirteen athletes (62%) completed longitudinal follow-up (4.8±1.9 months). The majority (69%) had reduction in cardiopulmonary symptoms, accompanied by improvement in peak VO2 and oxygen pulse, and reduction in resting and peak heart rate (all p<0.05). Conclusion: Despite a high burden of cardiopulmonary symptoms after COVID-19, no athlete had active inflammatory heart disease. CPET was clinically useful to reproduce symptoms with either normal testing or identification of abnormal spirometry as a potential therapeutic target. Improvement in post-COVID symptoms was accompanied by improvements in CPET parameters.